Implementasi Profil Pelajar Pancasila Melalui Pembelajaran PPKn di Sekolah Dasar - Susi Berliyana; Fatonah Salfadilah; Revika Amanda; Sri Yusma Daningsih; Lesti Tri Handayani (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This study aims to analyze the integration of the Pancasila Student Profile (PSP) within Civics Education (PPKn) learning in elementary schools through a descriptive qualitative library research approach. The research draws on 15 national journal articles published between 2020 and 2025 that discuss strategies, challenges, and outcomes of implementing the PSP in learning practices. The findings show that PSP values—such as mutual cooperation, independence, critical thinking, creativity, and noble character—are primarily integrated through classroom activities, project-based learning, and habituation programs aligned with the Merdeka Curriculum. However, several challenges persist, including limited teacher understanding, inconsistent school support, inadequate learning media, and insufficient alignment between curriculum expectations and classroom practices. The analysis also reveals that effective implementation requires strong teacher leadership, contextual learning strategies, and sustained school commitment to character development. The study contributes theoretically by deepening understanding of value-based learning and practically by offering recommendations for teachers and schools to optimize character-based PPKn instruction. Overall, the integration of PSP values strengthens students’ character formation and supports the development of a holistic learning environment consistent with Pancasila principles.